The Relationship of Balanced Nutrition Knowledge with the Attitudes and Behaviors of Young Women - Nizmah Nizmah; Sepsina Reski; Diah Retno Wahyunigrum; Joko Cahyono (Media Publikasi Cendekia Indonesia, 2024)
This study aims to determine the relationship between balanced nutrition knowledge with the attitudes and behaviors of adolescent girls. An analytical survey with a cross-sectional design was conducted in July – August 2023 at the Paqusata Youth Integrated Healthcare Center working area of the Teluk Lingga Health Center, East Kalimantan, Indonesia. A total of 51 adolescents were included as a sample using total sampling and setting inclusion and exclusion criteria. Data analysis using the Chi-Square test. Univariate tests showed respondents' age (31.4%), grade 10 (41.2%), mothers with high school education (43.1%), and parents' occupation was IRT (78.4%). Knowledge of balanced nutrition is mostly a good criterion (62.7%), attitudes are mostly good criteria (66.7%), and behaviour is mostly a good criterion (51%). The bivariate test showed knowledge of balanced nutrition with attitudes in adolescent girls with a value of p = 0.000. And knowledge of balanced nutrition with behaviour in adolescent girls with a value of p = 0.025. There is a relationship between knowledge of balanced nutrition and attitudes in adolescent girls. There is a relationship between knowledge of balanced nutrition and behaviour in adolescent girls. It is hoped that the management of the Puskesmas can provide regular nutrition socialization and education at the Adolescent Integrated Healthcare Center and in schools regarding balanced nutrition.